(untitled) (Journal of the Bangladesh Agricultural University, 2017)
The aim of the study was to identify the extent of the project objectives are implemented and the impact of the project. The sample size was determinate by using cluster sampling techniques with considering the design effect which was covered 1281 sample from ASA 518, BRAC 347and TMSS 415. Data was collected by pre-determine interview schedule, FGD, KII and observation methods in the year 2016. The collected data were analyzed by descriptive statistics and econometric model using the SPSS software. The result revealed that the project beneficiaries homestead, garden ponds and land on the amount of positive and negative impact on the amount of agricultural land and created employment of 2320 person in the beneficiary entrepreneurs 2104 people full-time and part-time jobs have been created. According to both the groups jobs have been created due to project activities in project area. The project has created 33432 agribusiness entrepreneurs and about three times a job was generated by them and 90524 persons employment in rural and semi-urban areas. It help to increase monthly income on an average 30.07% which contribute to socio-economic development of the area and economy through providing support to rural poor people and creation rural entrepreneurs. The credit diversion of producers, processors, marketers and input suppliers of beneficiary group was less by 8.09%, 29.01%, 20.37% and 17.80%, respectively. This study has been undertaken as an examining to assess the role and significance of agribusiness in Bangladesh along with the present situation and future prospective. Agribusiness plays a vital role to the increased income realized by the farmers. The study recommended that the agribusiness has positive impact on income of the farmers, increased commercialization and economic development in Bangladesh. J. Bangladesh Agril. Univ. 15(1): 62-72, January 2017